The immunology of the vermiform appendix: a review of the literature. (19th July 2016) - Kooij, I. A.; Sahami, S.; Meijer, S. L.; Buskens, C. J.; te Velde, A. A.
Summary: This literature review assesses the current knowledge about the immunological aspects of the vermiform appendix in health and disease. An essential part of its immunological function is the interaction with the intestinal bacteria, a trait shown to be preserved during its evolution. The existence of the appendiceal biofilm in particular has proved to have a beneficial effect for the entire gut. In assessing the influence of acute appendicitis and the importance of a normally functioning gut flora, however, multiple immunological aspects point towards the appendix as a priming site for ulcerative colitis. Describing the immunological and microbiotical changes in the appendix during acute and chronic inflammation of the appendix, this review suggests that this association becomes increasingly plausible. Sustained by the distinct composition of cells, molecules and microbiota, as well as by the ever more likely negative correlation between the appendix and ulcerative colitis, the idea of the appendix being a vestigial organ should therefore be discarded.